Effect of training phased distance training method the archer's shooting ability - Dwijawanti, Betaria; Satria, M. Haris (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2024)
This study aims to evaluate the effect of gradual distance drill method training on the shooting ability of archery athletes at Dega Archery School.  The research methods used were pre-experimental research methods with the design of a group pre-test and post-test design. The study sample consisted of 10 athletes selected based on a uniform ability level. Instrumental research using an archery accuracy test. Data analysis using paired t-test with SPSS version 23. The results showed a significant improvement in accuracy and consistency of shooting in the athletes who underwent the gradual distance drill method, indicating the method's effectiveness in improving shooting ability. This finding highlights the potential of the Gradual Distance Drill Method as a training strategy that can be used to enhance the performance of archery athletes. Conclusion The graded distance drill method can be used as a training strategy to improve the performance of archery athletes. Suggestions, further research could use larger sample sizes and tighter controls to provide an understanding of the effectiveness of the method in a broader context.